2018
DOI: 10.1016/j.isci.2018.03.020
|View full text |Cite|
|
Sign up to set email alerts
|

Tolerance of Perovskite Solar Cell to High-Energy Particle Irradiations in Space Environment

Abstract: SummaryMaterials to be used in the space environment have to withstand extreme conditions, particularly with respect to cosmic particle irradiation. We report robust stability and high tolerance of organolead trihalide perovskite solar cells against high-fluence electron and proton beams. We found that methylammonium and formamidinium-based lead iodide perovskite solar cells composed of TiO2 and a conductive polymer, as electron and hole transport materials, can survive against accumulated dose levels up to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
201
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(209 citation statements)
references
References 26 publications
(30 reference statements)
8
201
0
Order By: Relevance
“…Using ion irradiation in crystalline silicon with 0.2 at% displaced atom (equivalent to 1E13 He + cm −2 with MAPI), the signal was not measurable, and lower than for a bare Si wafer . This comparison emphasizes the outstanding radiation hardness of light emission properties: methylammonium lead iodide can withstand ion irradiation fluences about a factor 10 5 higher than crystalline silicon, which is consistent with what was found by other authors …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Using ion irradiation in crystalline silicon with 0.2 at% displaced atom (equivalent to 1E13 He + cm −2 with MAPI), the signal was not measurable, and lower than for a bare Si wafer . This comparison emphasizes the outstanding radiation hardness of light emission properties: methylammonium lead iodide can withstand ion irradiation fluences about a factor 10 5 higher than crystalline silicon, which is consistent with what was found by other authors …”
Section: Resultssupporting
confidence: 89%
“…The irradiation of solar cell devices with 68 MeV protons allowed to evidence that perovskite absorbers can withstand proton doses up to 10 12 cm −2 , which exceeds the damage threshold of c‐Si by almost 3 orders of magnitude. In the frame of photovoltaic devices, a very good tolerance to electron irradiation (1 MeV, up to 10 16 cm −2 ) and proton irradiation (50 keV, up to 10 15 cm −2 ) was also shown . Theoretical calculations revealed that the electronic properties of HOP materials are tolerant to defects because the intrinsic point defects and grain boundaries do not generate gap states, but the origin of this puzzling property is still under debate .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the extreme temperature in space could be controlled by optimizing encapsulation to guarantee device stability. More recently, it has been demonstrated that perovskites have excellent radiation hardness to high‐energy particles for space applications . However, light‐induced degradation is inevitable against its real application as light absorbers in solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others [24][25][26] have reported that the structural rearrangement from TP to OP causes a distinct hysteretic change in optical and transport properties as well as device behavior between heating and cooling cycles. Unless understood and mitigated, such hysteretic changes at low temperature may limit the use of perovskite solar cells in some specific applications, for example, aerospace applications, which require operation at extremely low temperatures [28] (<200 K).State-of-the-art perovskite films are polycrystalline, which leads to microscale inhomogeneities in a number of properties such as morphology and defect distributions [29][30][31][32] and, in turn, to local variations in the electronic environment for charge carriers. [24] These results provide hints that the thermal stability [27] and phase transition can be influenced by the local environment of the film due to interactions between the material and substrate as well as within the bulk film itself.…”
mentioning
confidence: 99%